P48 Attendance rates and response to pulmonary rehabilitation. (16th November 2010) - Nolan, CM; Ingram, KA; Fowler, RP; Clark, AL; Man, WD
Abstract : Background: Although randomised controlled trials and meta-analyses have demonstrated that pulmonary rehabilitation (PR) improves exercise capacity, there is a variability of response and a proportion of PR participants have not shown clincally significant improvements. We hypothesised that attendance record is an important determinant of exercise response to PR. Methods: 116 consecutive participants, who attended and completed an outpatient PR programme between September 2009 and June 2010, were included in the study. Subjects attended supervised PR twice per week for 8 weeks, with daily unsupervised home exercise. 107 subjects had pre- and post-PR data. Attendace rate at the supervised sessions was recorded, and good attendance was defined a priori as 75% or more attendance. Changes in incremental shuttle walk (ISW) pre- and post-PR were calculated for good and poor attendance groups and compared using Mann–Whitney test. Spearman rank correlation and univariate regression was used to assess the relationship between attendance rate and change in ISW following PR. Results: Results were expressed as mean (SD) or median (25th – 27th centiles). Patient baseline characteristics were as follows: 55M, 52F, age: 69 (63, 76), FEV1: 1.28 (0.85, 1.89), MRC dyspnoea score; 3 (3, 4), BMI: 27.4 (23.7, 32.1) and ISW: 180 (80, 320). Mean attendance rate was 83 (17)%. There was no significant difference in age, MRC dyspnoea score and ISW between good and poor attendance groups. Median change in ISW following PR was significantly better in the good attendance group compared with the poor attendance group (60 vs 10 m; <0.02). Although Spearman rank correlation was significant (Spearman r=0.21; p=0.03), there was no significant linear relationship (r2=0.01; p=0.35) between attendance rate and change in ISW following PR. Discussion: Patients attending more than 75% of PR sessions improve ISW distance in response to PR more than those attending less than 75% although the effects of confounding factors cannot be excluded. There is no linear relationship between attendance rate and improvement in ISW. There are likely to be multiple factors determining response to PR.